A 3D Multi-Phase Hydrodynamic Model for Cytokinesis of Eukaryotic Cells (Communications in Computational Physics, 2018)
In the late stage of the mitotic cycle of eukaryotic cells, cytokinesis ensuesduring which a parent cell replicates its nucleus with the necessary geneticalsubstances (i.e., DNAs and chromosomes) and splits into two similar offspring cells.This mitotic process involves complex chemical, biophysical and mechanical processeswhose details are just beginning to be unfolded experimentally. In this paper, we proposea full 3-D hydrodynamical model using a phase field approach to study the cellularmorphological change during cytokinesis. In this model, the force along the contractingring induced by remodeling of actin-myosin filament on cell cortex layer atthe division plane of the parent cell during cytokinesis, is approximated using a proxyforce anchored on the newly formed nuclei. The symmetric or asymmetric cell divisionis simulated numerically with the model. Our numerical results show that the locationof the division plane and the contracting force along the cytokinetic ring on the divisionplane are essential for the cell division. In addition, our numerical study also showsthat, during cytokinesis, surface tension of the cell membrane also contributes to thisprocess by retaining the morphological integrity of the offspring cells. This model andthe accompanying numerical simulation tool provide a solid framework to build uponwith more sophisticated whole cell models to probe the cell mitotic process.